Key Issues in Development and Application of the Sky-Based Internet of Things - Yongjian LIU; Bincheng LI; Yanzhe WANG (天地一体化信息网络)
The advantage and technical characteristics of the space-based internet of things(IoT) was analyzed and present status of existing space-based IoT system was brief description.The present situation of satellite communications industry was studied, combined with the development of other industries, suitability of space-based IoT, and users demand growth, in a macro position with current situation and perspective of industry market and development trend of space-based IoT was discussed, and the market space was predicted.The key technology of space-based IoT was analyzed, technical requirements and challenges were discussed according to access technology, networking, application layer.The perspective of development of space-based IoT in technical and market prospect was analyzed, the critical issues and key elements in the development and application of space-based IoT need to focus on were put forward, and made recommendations for the development of space-based IoT.